Explorers and Scientists in China's Borderlands, 1880-1950 - Glover, Denise Marie (Book collections on Project MUSE., 2011)
"Profiles pioneering Euro-American scientists and explorers in late-nineteenth- and early-twentieth-century China"--Provided by publisher.